2020
DOI: 10.1038/s41598-020-72575-6
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven malaria prevalence prediction in large densely populated urban holoendemic sub-Saharan West Africa

Abstract: Over 200 million malaria cases globally lead to half-million deaths annually. The development of malaria prevalence prediction systems to support malaria care pathways has been hindered by lack of data, a tendency towards universal “monolithic” models (one-size-fits-all-regions) and a focus on long lead time predictions. Current systems do not provide short-term local predictions at an accuracy suitable for deployment in clinical practice. Here we show a data-driven approach that reliably produces one-month-ah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…Our work shows the significance of continuous recording of dengue incidence for long periods and reinforces the relevance of ovitrap monitoring. From a broader point of view, the results presented here complement previous studies focused on the prediction of diseases such as rabies, influenza, and malaria 32 34 . Taken together, these works reinforce the potential of using machine learning and data mining as innovative and powerful tools to predict different diseases.…”
Section: Discussionsupporting
confidence: 76%
“…Our work shows the significance of continuous recording of dengue incidence for long periods and reinforces the relevance of ovitrap monitoring. From a broader point of view, the results presented here complement previous studies focused on the prediction of diseases such as rabies, influenza, and malaria 32 34 . Taken together, these works reinforce the potential of using machine learning and data mining as innovative and powerful tools to predict different diseases.…”
Section: Discussionsupporting
confidence: 76%
“…Nonetheless, some studies have shown high burdens of transmission reported in large, densely populated urban holoendemic settings, albeit among children (e.g., Brown et al, 2020). Thus, the transmission of these freshwater-related diseases has demonstrated clear patterns geographically and across different demographic groups.…”
Section: Socio-economic and Health Impacts Of Water-related Vector-bo...mentioning
confidence: 99%
“…In the current context of climate change and rapid and unplanned urbanization in SSA, there is an urgent need to deepen the knowledge of intra‐urban malaria risk and to develop predictive maps for SSA cities, where malaria risk is known to be highly heterogeneous (Brown et al., 2020 ; Mathanga et al., 2016 ). However, such attempts have always been constrained by the availability and quality of malaria survey data, which, although improving considerably, remain limited for studying malaria risk at the intra‐urban scale.…”
Section: Discussionmentioning
confidence: 99%